Human Leukocyte Antigen Class I and II Alleles and Cervical Adenocarcinoma - Safaeian, Mahboobeh; Johnson, Lisa G.; Yu, Kai; Wang, Sophia S.; Gravitt, Patti E.; Hansen, John A.; Carrington, Mary; Schwartz, Stephen M.; Gao, Xiaojiang; Hildesheim, Allan; Madeleine, Margaret M. (Frontiers in Oncology, 2014)
Associations between human leukocyte antigens (HLA) alleles and cervical cancer are largely representative of squamous cell carcinoma (SCC), the major histologic subtype. We evaluated the association between HLA class I (A, B, and C) and class II (DRB1 and DQB1) loci and risk of cervical adenocarcinoma (ADC), a less common but aggressive histologic subtype. We pooled data from the Eastern and Western US cervical cancer studies, and evaluated the association between individual alleles and allele combinations and ADC (n=630 ADC; n=775 controls). Risk estimates were calculated for 11 a priori (based on known associations with cervical cancer regardless of histologic type) and 38 non a priori common alleles, as odds ratios (OR) and 95% confidence intervals (CI), adjusted for age and study. In exploratory analysis, we compared the risk associations between subgroups with HPV16 or HPV18 DNA in ADC tumor tissues in the Western US study cases and controls. Three of the a priori alleles were significantly associated with decreased risk of ADC (DRB1*13:01 (OR=0.61; 95%CI:0.41-0.93), DRB1*13:02 (OR=0.49; 95%CI:0.31-0.77), and DQB1*06:03 (OR=0.64; 95%CI:0.42-0.95)); one was associated with increased risk (B*07:02(OR=1.39; 95%CI:1.07-1.79)). Among alleles not previously reported, DQB1*06:04 (OR=0.46; 95%CI: 0.27-0.78) was associated with decreased risk of ADC and C*07:02 (OR=1.41; 95%CI:1.09-1.81) was associated with increased risk. We did not observe a difference by histologic subtype. ADC was most strongly associated with increased risk with B*07:02/C*07:02 alleles (OR=1.33; 95%CI:1.01-1.76) and decreased risk with DRB1*13:02/DQB1*06:04 (OR=0.41; 95%CI:0.21-0.80). Results suggest that HLA allele associations with cervical ADC are similar to those for cervical SCC. An intriguing finding was the difference in risk associated with several alleles restricted to HPV16 or HPV18 related tumors, consistent with the hypothesis that HLA recognition is HPV type specific.